The Representation of Emotion Inferences. Issue 8 (14th September 2021) - Mumper, Micah L.; Gerrig, Richard J.
ABSTRACT: While research has repeatedly found evidence that readers infer characters' emotions, we investigate three outstanding questions about the content and time course of such inferences. We ask whether even simple narratives give rise to emotion inferences, in what form such inferences are encoded into long-term memory, and whether they are uniquely bound to the character whose actions prompted the inference. To address these issues, we had participants read simple, sentence-long stories that allowed ready emotion inferences. Compared to performance on control stories, participants took longer to reject the implied emotion term in an immediate paradigm (Experiment 1) and were less accurate in a delayed paradigm when primed by the name of the character who experienced the emotion (Experiment 2). In Experiment 3, we primed participants in a delayed recognition paradigm with either the name of the character who experienced the emotion or a secondary character who did not. Participants were less accurate in rejecting the implied emotion term when primed by both character names. These results suggest that readers can encode emotion inferences based on simple narratives and that they encode those inferences into long-memory with minimal content. In addition, those emotion inferences may be activated from features of the general narrative situation, rather than only by the character whose actions or experiences prompted the inference.